Performance of the Precision Time Protocol for clock synchronisation in smart grid applications. Issue 5 (29th May 2013) - Kassouf, Marthe; Dupont, Louis; Béland, Jean; Fadlallah, Adam
ABSTRACT: Accurate time stamping is essential for reliable operation of the automation and control systems used across a smart grid. This paper investigates the performance of the Precision Time Protocol (PTP) for time distribution over the telecommunication networks interconnecting such systems. Distributed clocks are arranged in a PTP master‐slave hierarchy and can be synchronised to an international time standard with sub‐microsecond accuracy. Using Hydro Québec's telecommunications facilities, we investigate the synchronisation error that is observed using some of the latest PTP clock prototypes over a widely spread network. As such, field trials are performed by deploying PTP master and slave clocks in distant sites of Hydro Québec's wide area network (WAN). A thorough analysis of these trial outcomes is further conducted using laboratory experiments that point out the impact of different parameters such as the PTP messages rate, as well as the link bandwidth and asymmetry. Our analysis leads to important criteria for optimal PTP system design in a WAN environment using appropriate clock and network parameter settings. Improving the PTP clocks internal features is also part of this optimal design, since it is necessary for maintaining the required synchronisation performance in power grid applications running under scarce communication network bandwidth conditions. Copyright © 2013 John Wiley & Sons, Ltd. Abstract : This paper considers the performance of the Precision Time Protocol (PTP) for clock synchronisation over a wide area network (WAN), such as Hydro Québec's WAN, where typical power grid control and surveillance applications employ distributed systems requiring an accurate system‐wide sense of time. By using some of the latest PTP clock prototypes, we conduct WAN field trials and further investigate their outcomes over a laboratory network to better analyse the synchronisation accuracy impact of different network parameters and clock settings. Our analysis yields important criteria for optimal PTP system design in a WAN environment where the accuracy requirements can be in the sub‐millisecond and sub‐microsecond ranges.